Transcriptome Reveals Cathepsin K in Periodontal Ligament Differentiation. (August 2016) - Yamada, S.; Ozaki, N.; Tsushima, K.; Yamaba, S.; Fujihara, C.; Awata, T.; Sakashita, H.; Kajikawa, T.; Kitagaki, J.; Yamashita, M.; Yanagita, M.; Murakami, S.
Periodontal ligaments (PDLs) play an important role in remodeling the alveolar bond and cementum. Characterization of the periodontal tissue transcriptome remains incomplete, and an improved understanding of PDL features could aid in developing new regenerative therapies. Here, we aimed to generate and analyze a large human PDL transcriptome. We obtained PDLs from orthodontic treatment patients, isolated the RNA, and used a vector-capping method to make a complementary DNA library from >20, 000 clones. Our results revealed that 58% of the sequences were full length. Furthermore, our analysis showed that genes expressed at the highest frequencies included those for collagen type I, collagen type III, and proteases. We also found 5 genes whose expressions have not been previously reported in human PDL. To access which of the highly expressed genes might be important for PDL cell differentiation, we used real-time polymerase chain reaction to measure their expression in differentiating cells. Among the genes tested, the cysteine protease cathepsin K had the highest upregulation, so we measured its relative expression in several tissues, as well as in osteoclasts, which are known to express high levels of cathepsin K. Our results revealed that PDL cells express cathepsin K at similar levels as osteoclasts, which are both expressed at higher levels than those of the other tissues tested. We also measured cathepsin K protein expression and enzyme activity during cell differentiation and found that both increased during this process. Immunocytochemistry experiments revealed that cathepsin K localizes to the interior of lysosomes. Last, we examined the effect of inhibiting cathepsin K during cell differentiation and found that cathepsin K inhibition stimulated calcified nodule formation and increased the levels of collagen type I and osteocalcin gene expression. Based on these results, cathepsin K seems to regulate collagen fiber accumulation during human PDL cell differentiation into hard tissue-forming cells.